2017
DOI: 10.1097/md.0000000000007385
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for patients with World Health Organization grade III meningiomas treated at a single center

Abstract: We analyzed the characteristics of patients with World Health Organization (WHO) grade III meningioma to identify factors that may predict tumor recurrence and overall survival (OS).We retrospectively reviewed the patients diagnosed with WHO grade III meningioma who were surgically treated at our institute between 2008 and 2016. Survival outcome was assessed by Kaplan–Meier analysis. Cox regression analyses were performed to identify the prognostic factors associated with tumor recurrence and OS.Forty-two pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…A total of 43 studies published from 1996 to 2017 with 5012 patients were included in the final meta-analysis. [ 16 , 19 24 , 31 66 ] Among these studies, 17 studies were conducted in Eastern countries and 26 studies in Western countries; the sample size ranged from 23 to 422; 4 studies comprised only low-grade (grade I) meningioma patients, 18 studies only high-grade (grade II/III) patients, and 21 studies both low- and high-grade patients; 14 articles reported OS and 38 articles reported D/P/RFS; HR and 95% CIs data were extracted directly from 25 studies, or were calculated from Kaplan–Meier survival curves in 18 studies. According to the quality assessment, 7 studies had quality scores of 7 or less, and the rest 36 studies had a score of more than 7 (see Table S2, Supplemental Content, which illustrates the quality assessment of included studies).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 43 studies published from 1996 to 2017 with 5012 patients were included in the final meta-analysis. [ 16 , 19 24 , 31 66 ] Among these studies, 17 studies were conducted in Eastern countries and 26 studies in Western countries; the sample size ranged from 23 to 422; 4 studies comprised only low-grade (grade I) meningioma patients, 18 studies only high-grade (grade II/III) patients, and 21 studies both low- and high-grade patients; 14 articles reported OS and 38 articles reported D/P/RFS; HR and 95% CIs data were extracted directly from 25 studies, or were calculated from Kaplan–Meier survival curves in 18 studies. According to the quality assessment, 7 studies had quality scores of 7 or less, and the rest 36 studies had a score of more than 7 (see Table S2, Supplemental Content, which illustrates the quality assessment of included studies).…”
Section: Resultsmentioning
confidence: 99%
“…L. Bertero et al (2019) выявили зависимость течения заболевания от наличия или отсутствия «горячих точек» (очагов пролиферативной активности) при исследовании с Ki67 [83]. В классификации ВОЗ 2016 г. отсутствуют рекомендации по определению степени анаплазии в менингиомах на основании уровня пролиферативной активности по Ki67 [2, [84][85][86][87]. Вопрос значения уровня пролиферативной активности для определения степени анаплазии в менингиомах до сих пор остается открытым, и в классификации ВОЗ 2021 г., наконец-то, появились некоторые данные по поводу молекулярно-генетического статуса менингиом, однако ряд исследователей указывает на более широкое разнообразие генетики менингиом [88][89][90][91][92].…”
Section: патоморфологияunclassified
“…58 The female predominance amongst all meningioma patients is not apparent in WHO grade 3 meningiomas. It is not clear whether male sex is predominant amongst patients with WHO grade 3 meningioma, as some studies report an approximately even sex-distribution, [58][59][60][61][62] and others report a tendency of more males. 63,64 WHO grade 3 meningiomas tend to arise in non-skull base locations, preferably at the convexity and falx, 65 but skull base meningiomas can also be WHO grade 3 meningiomas.…”
Section: Who Grade 3 Meningiomamentioning
confidence: 99%